Weather-resistant pearlescent pigment
By using transparent small small sheet substrates and high refractive index metal oxide layers in pearl pigment, and add rare earth metal oxides and organic official surface modification top coating, the existing pigment is to be resistant to weather tolerance Reinforced the problem of gloss and color changes in the test realizes stable gloss and color.
Patent Information
- Application Number
- CN202380047324.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-22
- Filing Date
- 2023-12-07
- Publication Date
- 2025-01-24
AI Technical Summary
Existing weather-resistant pearlescent pigments are prone to cause gloss loss and color changes in weather resistance enhancement tests, especially under the action of ultraviolet light, which leads to accelerated degradation of organic compounds.
The weather -resistant pearly pigment with a transparent small sheet -like substrate and a high refractive index metal oxide layer is used, and the top coating containing rare earth metal oxides and organic official surface modification on its top.
This weather-resistant pearlescent pigment can successfully pass the enhanced weather resistance test, maintain gloss and color stability, and avoid unnecessary color changes and gloss loss.
Smart Images

Figure CN119365550A_ABST
Abstract
Description
[0001] The present invention relates to weather stable pearlescent pigments which, due to their topcoat, have no loss of gloss in intensive weathering tests and no noticeable color change.
[0002] Pearlescent pigments containing titanium dioxide in the top layer or from particles of TiO 2 The prepared pearlescent pigments have a certain photocatalytic activity. If ultraviolet (UV) light subsequently acts on the pearlescent pigment in the presence of water and oxygen, the UV activity of the pearlescent pigment can lead to accelerated degradation of organic compounds, such as adhesive matrices. Even a certain proportion of UV present in daylight can lead to this reaction, i.e. for applications such as automotive painting, which are directly exposed to the weather, specially stabilized pearlescent pigments must be used. In order to counteract this harmful influence for outdoor applications, the pearlescent pigments can be coated with various protective coatings to reduce the photoactivity.
[0003] EP 0 141 174 describes pearlescent pigments with improved weathering resistance, which have a protective coating consisting essentially of a rare earth metal compound and a polysiloxane, wherein the rare earth metal compound is defined as cerium oxide. In addition, the protective coating used in aqueous suspension may also include zinc salts and / or aluminum salts or silicates. The polysiloxane is applied together with a silicate or aluminum oxide coating.
[0004] EP 0 342 533 discloses zirconium oxide-coated pigments to which a layer consisting of a hydrated metal oxide of cobalt, manganese or cerium can be applied. The pigments thus treated are said to be very suitable for use in nonaqueous coating systems, but are still unsuitable for water-dilutable coating materials according to EP 632 109, since they lead to the formation of microbubbles in the coating film.
[0005] According to the teaching of EP 0 632 109, three protective layers are applied to a platelet-shaped substrate coated with metal oxides. In the first stage, SiO 2 In the second stage, a hydroxide or oxide hydrate of cerium, aluminum or zirconium is applied, and in the third stage at least one hydroxide or oxide hydrate of cerium, aluminum or zirconium and an organic coupling agent are applied. In addition, the coupling agent must be hydrolyzed before bonding to the pigment surface; according to the teaching of EP 0 888 410 B1, only up to 60% of the coupling agent added can be bonded to the pigment surface.
[0006] EP 0 888 410 B1 discloses modified pearlescent pigments based on platelet-shaped substrates coated with metal oxides. According to the teaching of EP 0 888 410 B1, the top layer consists of at least two oxides, oxide mixtures or mixed oxides selected from silicon dioxide, aluminum oxide, cerium oxide, titanium oxide or zirconium oxide and a water-based oligomeric silane system.
[0007] EP 0 649 886 provides pearlescent pigments having a titanium dioxide or iron oxide coating which are subsequently coated in aqueous phase with a combination of cerium and aluminum oxide hydrates and then dried.
[0008] US 2011 / 0118384 A1 discloses weather-resistant pearlescent pigments having a protective layer from copolymers of different metal oxides and acrylates.
[0009] According to the teaching of EP 1 203 795, pearlescent pigments can comprise a layered structure in which a first layer comprises an oxide hydrate of silicon or aluminum and a subsequent second layer comprises an oxide hydrate of silicon, aluminum, zirconium or cerium, wherein the composition of the first layer differs from the composition of the second layer. The pearlescent pigments also comprise a third layer of at least one organic hydrophobic coupling agent which does not react with the binder, i.e. the coating system.
[0010] EP 1682622 A1 discloses weather-resistant pearlescent pigments having a top coating comprising a first layer of cerium oxide followed by a layer of SiO 2 layer and organic surface modification.
[0011] US2019 / 0169439 A1 discloses a weather-resistant pearlescent pigment having a protective layer, wherein the protective layer contains at least one rare earth metal oxide selected from silicon, aluminum or zirconium and a mixture thereof and at least one metal oxide, and particularly mentions that the rare earth metal oxide is Ce. 2 O 3 , which is used in multiple embodiments.
[0012] US 2014 / 4018439 A1 discloses weather-resistant pearlescent pigments, wherein the top coating comprises cerium oxide as a single metal oxide layer and is then organically functionalized.
[0013] US 2015 / 0259563 A1 discloses weather-resistant pearlescent pigments, wherein in the topcoat layer there is first a metal oxide layer of tin, then a cerium oxide layer, and finally an organic surface modification with oligomeric silanes.
[0014] In practice, all weatherable topcoats using cerium oxide are limited in the amount of cerium oxide used, because cerium oxide has a pale yellow absorption color. Too large an amount can lead to an undesirable color change of the entire pearlescent pigment.
[0015] On the other hand, new customers demand a more intensive method for testing weathering resistance, which is a combination of two known methods. First, the pearlescent pigments are coated in a suitable basecoat on KTL panels, with 1K basecoats being used according to automotive requirements. These coatings are first treated in the xenon test for 1000 to 4000 hours and immediately afterwards tested for condensation water. This test sequence simulates the very harsh conditions in very sensitive paint coating systems. In many cases, this leads to irreversible UV reactions and swelling phenomena, which ultimately lead to unwanted color changes in the paint application or a significant reduction in the gloss properties.
[0016] Therefore, one object of the present invention is to provide weather-resistant pearlescent pigments which can successfully pass this intensive weathering test procedure but do not change their interference color too strongly compared to the initial pearlescent pigment without a topcoat layer and do not suffer a significant loss of gloss.
[0017] This object can be solved by providing a weather-resistant pearlescent pigment having a base pearlescence and an interference color, the pigment comprising a transparent platelet-shaped substrate and at least one metal oxide layer having a refractive index > 1.8, and having a weather-resistant top coating on top of the base pearlescent pigment, the weather-resistant top coating comprising at least one metal oxide and an organic functional surface modification, wherein:
[0018] a) For a base pearlescent pigment having a silver interference color, the weather-resistant top coating is composed of a rare earth metal M selected from Y, La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu and mixtures thereof 1 A first metal oxide composition, or
[0019] b) For base pearlescent pigments with colored interference colors or silver interference colors, the weather-resistant top coating comprises a rare earth metal M selected from Y, La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu and mixtures thereof. 1 A first metal oxide, and a second metal M selected from Si, Al, Zn, Mg, Zr, Sn and a mixture or a combination thereof 2 The second metal oxide,
[0020] And in each case of a) or b), the organofunctional surface modification comprises an organofunctional silane or a water-based pre-condensed organofunctional silane.
[0021] Preferred embodiments of the weather-resistant pearlescent pigment are further described in claims 2-11.
[0022] Another object of the present invention is to provide a simple method for preparing weather-resistant pearlescent pigments.
[0023] This object can be achieved by providing a method for preparing a weather-resistant pearlescent pigment, the method comprising the following steps:
[0024] i) suspending the base pearlescent pigment in a solvent,
[0025] iia) coating the base pearlescent pigment in a solvent from step i) with a precursor of a rare earth metal oxide at a predetermined pH of 1 to obtain a rare earth metal oxide layer, or
[0026] iib) coating the base pearlescent pigment in solvent from step i) by one of the following methods:
[0027] iib1): using a precursor of a rare earth metal oxide at a predetermined pH 1 to obtain a rare earth metal oxide layer, and then coating the pearlescent pigment from this step with a precursor of a second metal oxide at a predetermined pH 2 to obtain a second metal oxide, or
[0028] iib2): using a precursor of a second metal oxide at a predetermined pH of 2 to form a second metal oxide, and then coating the pearlescent pigment with a precursor of a rare earth metal oxide at a predetermined pH of 1 to obtain a rare earth metal oxide layer, or
[0029] iib3): coating is performed using a precursor of a rare earth metal oxide together with a precursor of a second metal oxide at a predetermined pH 3, wherein the pH 3 is equal to or preferably between pH 1 and pH 2,
[0030] iii) coating the pearlescent pigment in solvent from step iia) or step iib) with an organofunctional silane or a water-based precondensed organofunctional silane, and
[0031] iv) isolating the coated pearlescent pigment, optionally washing with a solvent and drying at a temperature in the range of 80-160°C.
[0032] A preferred embodiment of the method is as described in claim 13.
[0033] Basic pearlescent pigment:
[0034] Natural mica is usually the thinnest transparent substrate, which requires a larger amount of refractive index metal oxides, especially TiO 2 , which results in higher photoactivity. Therefore, a more resistant top coat is needed here.
[0035] On the other hand, the optical properties of the basic pearlescent pigments based on synthetic substrates have optically very high-quality properties. "Optically very high-quality properties" means in particular the excellent gloss and color purity of the pearlescent pigments in the application medium.
[0036] Therefore, the situation that these optical properties are disturbed by the top coating is a serious disadvantage. The transparent platelet-shaped synthetic substrate is preferably selected from synthetic mica platelets, glass platelets, SiO 2 Small piece, Al 2 O 3 flakes, synthetic boehmite flakes, BiOCl flakes and mixtures thereof, more preferably selected from synthetic mica flakes, glass flakes, Al 2 O 3 Platelets and mixtures thereof. The platelet-shaped synthetic substrate is particularly preferably selected from glass platelets, synthetic mica platelets and mixtures thereof.
[0037] The above-mentioned synthetic substrates are known from patent applications and patent series. If, for example, the platelet-shaped synthetic substrate consists of glass flakes, then in the present invention, preference is given to using those synthesized according to the methods described in EP 0 289 240 A1, WO 2004 / 056716 A1 and WO 2005 / 063637 A1. Glass flakes that can be used as substrates can, for example, have a composition corresponding to the teaching of EP 1 980 594 B1.
[0038] The glass flakes described in these documents are also called glass flakes and are characterized in that they have a particularly uniform surface and thickness. The thickness of the glass flakes preferably varies with a standard deviation of at most 20%, more preferably at most 15%, and even more preferably at most 10%. The average thickness of the glass flakes is in the range of 20-2,000 nm, preferably in the range of 100 to less than 1,000 nm.
[0039] These glass flakes are preferably those which are produced according to the following process (see EP 0 289 240 B1):
[0040] - Add the stream of molten glass into the rotating cup in a downward direction,
[0041] - The glass melt is made to flow over the edge of the cup to force it into the gap between two plates around the cup, where the movement of the material is in the radial direction and is affected by the air flow between these plates to propel the radial flow in the radial direction, thereby keeping it flat and breaking into thin sheets when the material solidifies.
[0042] Pearlescent pigments based on synthetic substrates having optically very high quality are also known from EP 2 217 664 B1. It can be seen from this that substrates having a narrow size distribution surprisingly can provide pearlescent pigments having particularly high color purity and high gloss.
[0043] In an embodiment of the present invention, the weather-resistant pearlescent pigment of the present invention has a cumulative frequency distribution of a volume average size distribution function, wherein D 10 , D 50 and D 90 Value, wherein this cumulative frequency distribution has a span ΔD in the range of 0.7-1.4. The span ΔD is calculated according to formula (I):
[0044] ΔD=(D 90 -D 10 ) / D 50 (I).
[0045] According to the present invention, the span ΔD is used to characterize the particle size distribution. The smaller the span, the narrower the particle size distribution. In a particularly preferred embodiment, the weather-resistant pearlescent pigment of the present invention has a span ΔD in the range of 0.75-1.3, more preferably in the range of 0.8-1.2, and even more preferably in the range of 0.85-1.1.
[0046] When the span ΔD is greater than 1.4, pearlescent pigments of sufficiently pure color are not obtained. Within the framework of conventional processes, pearlescent pigments having a size distribution span of less than 0.7 can only be prepared in a very cumbersome manner and are therefore no longer economically viable.
[0047] Pearlescent pigments having the above-mentioned preferred span ΔD values have excellent color purity. This is especially true for those pearlescent pigments in which the average thickness of the substrate is 500-2000 nm, more preferably 500-1200 nm.
[0048] These parameters of the size distribution function and the average thickness of the preferred pearlescent pigment substrate thus interact in a synergistic manner with the weather-resistant coatings of the invention. In such pearlescent pigments of optically high quality, even small optical losses due to insufficient stability or due to excessively thick or optically distorting weather-resistant layers (e.g. swelling of these layers) can have a very distorting effect.
[0049] The weather-resistant pearlescent pigment of the present invention may have any average particle size D 50 The pigment of the present invention has a D 50 The pigments of the present invention preferably have a D value in the range of 3 to 80 μm. 50 Values, particularly preferably 7 to 56 μm, very particularly preferably 9 to 40 μm.
[0050] D of the pigment of the present invention 10 The value is preferably in the range of 1-25 μm. The pigments of the present invention preferably have a D 10Values, particularly preferably 3-18 μm, very particularly preferably 4-14 μm.
[0051] D of the pigment of the present invention 90 The value is preferably in the range of 6-250 μm. The pigments of the present invention preferably have a D 90 value.
[0052] The cumulative frequency distribution of the volume average size distribution function obtained by laser diffraction method is D 10 , D 50 or D 90 Value, which means that 10%, 50% or 90% of the pigments according to the invention have a diameter that is equal to or smaller than the specified value in each case. Here, the size distribution curve of the pigment is preferably measured using an apparatus from Malvern (apparatus: MALVERN Mastersizer 2000) according to the manufacturer's information. If a Mastersizer 3000 apparatus is used, it is recommended to use the built-in "Mastersizer 2000" module for measurement. The signal of the scattered light is evaluated according to the Fraunhofer approximation.
[0053] The average thickness of the platelet-shaped transparent substrate to be coated is preferably in the range of 50 nm to 5000 nm, more preferably in the range of 60 nm to 3000 nm, particularly preferably in the range of 70 nm to 2000 nm.
[0054] In one embodiment of the present invention, as the flake-shaped transparent substrate to be coated, the average thickness of the glass flakes is preferably in the range of 750nm to 1500nm. Such glass flakes are widely commercially available. Thinner glass flakes also provide advantages. Thinner substrates make the total layer thickness of the pigment of the present invention smaller. For glass flakes, the average thickness is in the range of 100nm to 700nm, more preferably in the range of 150nm to 600nm, particularly preferably in the range of 170nm to 500nm, further particularly preferably in the range of 200nm to 400nm, and these glass flakes are also preferred substrates according to the present invention.
[0055] In a further embodiment, the average thickness of the synthetic mica as the platelet-shaped substrate to be coated is preferably in the range of 100 nm to 700 nm, more preferably in the range of 120 nm to 600 nm, particularly preferably in the range of 140 nm to 500 nm, and further particularly preferably in the range of 150 nm to 450 nm.
[0056] If, for example, high-refractive metal oxides are used to coat small platelet-shaped transparent substrates with an average thickness of less than 50 nm, very brittle pigments are obtained, which can even break when added to the application medium, resulting in a significant reduction in gloss. In addition, the coating times when coating these thin substrates with, for example, high-refractive metal oxides are very long, which is due to the large specific surface area of these small platelet-shaped transparent substrates, i.e. the surface area per unit weight of the pigment, which leads to high production costs. When the average substrate thickness is greater than 5000 nm, the basic pearlescent pigment will be too thick overall. This can be associated with a poorer specific hiding power, which refers to the coverage area per unit weight of the pigment according to the invention, which is associated with a lower plane-parallel orientation in the application medium. The poorer orientation, in turn, leads to a reduction in gloss.
[0057] In a preferred embodiment, the standard deviation of the thickness of the artificial substrate is 15 to 100%, particularly preferably 20 to 70%, further particularly preferably 22 to 40%.
[0058] When the standard deviation is below 15%, a color-flop effect pigment is obtained. When the standard deviation is above 100%, a significantly thicker pigment is contained in the entire pigment system, resulting in poorer orientation and, in turn, loss of gloss.
[0059] The average thickness is determined using cured coating films in which the effect pigments are essentially in a plane-parallel orientation to the substrate. For this purpose, cross-sections of the cured coating films are examined by scanning electron microscopy (SEM), wherein the thickness of at least 100 pearlescent pigments is measured and statistically averaged.
[0060] The flake-shaped transparent substrate used according to the present invention can be a coated or uncoated flake-shaped substrate. For example, a low refractive index layer, such as Al 2 O 3 and / or SiO 2 However, the high refractive index layer is preferably applied as the outermost layer. It is also possible to apply a very thin SnO 2 layer, which enables the subsequent coating of TiO 2 The layer is rutile. “Rutile” means that the applied TiO 2 It does not exist in the anatase structure, but causes the formation of the rutile structure. However, the rutile structure can also be formed by the combined application of SnO 2 and TiO 2 This leads to the application of TiO with a rutile structure. 2 In terms of the SnO layer alone 2 Layers are not strictly necessary.
[0061] According to a preferred variant of the invention, uncoated platelet-shaped substrates are used.
[0062] The platelet-shaped substrate is coated with at least one high-refractive metal oxide layer, resulting in a conventional interference-based pearlescent effect. Within the framework of the present invention, a high-refractive metal oxide layer is understood to mean a layer having a refractive index >1.8, preferably >2.0.
[0063] At least one high refractive index layer preferably comprises or consists of a metal oxide, metal hydroxide and / or hydrated metal oxide selected from the group consisting of: TiO 2 , Fe 2 O 3 , Fe 3 O 4 、TiFe 2 O 5 , Fe 2 Ti 3 O 9 、FeTiO 3 、ZnO、SnO 2 , CoO, Co 3 O 4 、ZrO 2 Cr 2 O 3 , VO 2 、V 2 O 3 、(Sn,Sb)O 2 and mixtures thereof.
[0064] The at least one high-refractive-index metal oxide layer particularly preferably comprises or consists of a metal oxide, metal hydroxide and / or hydrated metal oxide selected from the group consisting of: TiO 2 , Fe 2 O 3 , Fe 3 O 4 、TiFe 2 O 5 , Fe 2 Ti 3 O 9 、FeTiO 3 and mixtures thereof.
[0065] In some embodiments, the transparent substrate is coated with only one (number: 1) high refractive index metal oxide layer, which is preferably selected from TiO 2 , Fe 2 O 3 、TiFe 2 O 5 , Fe 2 Ti 3O 9 、FeTiO 3 and mixtures thereof.
[0066] In a very particularly preferred embodiment, the substrate is coated with only one (number: 1) high-refractive-index metal oxide layer consisting of rutile-modified TiO 2 In the sense of the present invention, rutile-modified (or rutile-type TiO 2 ) refers to at least 99% by weight of TiO 2 Present as rutile, where wt% represents the total TiO in the corresponding layer 2 content.
[0067] In a further particularly preferred embodiment, the color-producing high refractive index coating comprises rutile TiO 2 , namely rutile-modified TiO 2 , its content is 30-80% by weight relative to the total weight of the pearlescent pigment. In particular, particularly strong third-order interference hues are usually within this range. Rutile TiO 2 The proportion of the coating material is further preferably in the range from 40 to 70% by weight, more preferably from 45 to 60% by weight, in each case relative to the total weight of the pearlescent pigments.
[0068] Independently of the fineness of the platelet substrate and further depending on the specific surface area, rutile TiO 2 These dosage ratios correspond to rutile TiO 2 The preferred average thickness of the layer is 80-280 nm. Rutile TiO 2 The average layer thickness is particularly preferably in the range from 100 to 270 nm.
[0069] At these layer thicknesses, third-order interference colors are generally obtained. 2 The layer thickness is large, so the pigments have a particularly high photocatalytic activity. Therefore, under the action of UV radiation, undesirable color fading or TiO-containing 2 The coating of pigment is discolored.
[0070] In some embodiments, the base pearlescent pigment has a so-called "spacer layer" located between two high refractive index layers. This spacer layer is porous, has large voids and specific connections, and has a very low effective refractive index. Such pearlescent pigments are described in EP3034562 B1, EP 3034563 B1, EP 3034564 B1 and WO 2016 / 097421 A1.
[0071] In the context of the present invention, a distinction is made between base pearlescent pigments having a “silver” or “tinted” interference color.
[0072] For the purposes of the present invention, a base pearlescent pigment having a "silver" interference color is defined as a base pearlescent pigment having a chromaticity value C* 15° ≦20, preferably ≦18, more preferably ≦15, very preferably ≦10. The C* of the base pearlescent pigment having a "silver" interference color of the present invention is 15° It is preferably in the range of 1 to ≦20, more preferably in the range of 2 to ≦19, more preferably in the range of 3 to ≦18, and particularly preferably in the range of 4 to ≦17.
[0073] In the case of multilayer pearlescent pigments, these effect pigments have a colored appearance in addition to their silvery interference color when viewed from the outside at the specular angle. This colored appearance can be caused by the inherent color of the coating material and its layer thickness, which depends on the properties of the coating of the flake-shaped transparent substrate. In view of the high gloss, any possible absorption color will be more shiny at the specular angle, and the overall appearance of the multilayer pearlescent pigment of the present invention will appear silver to the observer. In other embodiments, the silver interference color can also have a slightly colored hue at the viewing angle, but the observer then mainly perceives the silver appearance.
[0074] The color values are determined by coating a nitrocellulose varnish (Dr. Renger Erco Bronzemischlack 2615e; Morton) containing 6.0% by weight of base pearlescent pigment onto a BYK-Gardner black / white drawdown chart (Byko-Chart 2851), wherein the % by weight data are based on the total weight of the varnish, according to D 50 The wet film thickness was selected to provide adequate hiding power based on the value and pigment opacity; and then dried at room temperature. The drawdown forms were then color evaluated using BYK-MAC (BYK Gardner), where the measurements were made on a black background of the drawdown form. The angle of incidence was 45° and the chromaticity values used were those obtained at an observation angle of 15°.
[0075] Similarly, a base pearlescent pigment having a "tinted interference color" under these conditions is defined as having C* 15° >20, preferably >18, more preferably >15, very preferably >10. C* 15° These lower limits of values are to be interpreted as being complementary to those defined above for silver base pearlescent pigments.
[0076] The color change of the base pearlescent pigment caused by the top coating can affect the interference color. However, this is significantly more serious when the base pearlescent mass tone is affected. Therefore, in the present invention, the change of the mass tone caused by the top coating is mainly reduced. This change of the mass tone can be best measured on a white background, and its details are shown in the experimental part below.
[0077] Weather Resistant Top Coat:
[0078] In the present invention, the term "rare earth metal oxide" refers not only to oxides but also to rare earth metal hydroxides or hydrated rare earth metal oxides and mixtures thereof. Similarly, the term "second metal oxide" of the top coating or any other metal oxide of the top coating refers not only to oxides but also to second metal hydroxides or second metal oxide hydrates and mixtures thereof. The same applies to specific chemical formulas. For example, "Sm 2 O 3 " may also include hydroxides or oxide hydrates of Sm(III) and mixtures thereof.
[0079] The metal oxides of the weatherable topcoat may be calcined prior to coating with the organofunctional agent. However, in most cases these coatings are not calcined so hydroxides and oxide hydrates may be present.
[0080] The rare earth metal oxide for the corresponding metal oxide is selected from the metals Y, La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu and mixtures thereof. Preferably, the rare earth metal oxide for the corresponding metal oxide is selected from the metals La, Pr, Nd, Sm, Eu, Gd, Ho, Yb and mixtures thereof, more preferably selected from Pr, Nd, Sm, Eu, Gd, Ho, Yb and mixtures thereof, most preferably selected from Nd, Sm, Yb, Eu, Ga and mixtures thereof.
[0081] As for the rare earth metal oxide, it is preferred to mainly use metal oxides having a trivalent formal oxidation state. Therefore, preferably, 50-100 atomic %, more preferably 70-99 atomic % of the rare earth metal M 1 Metal oxides are based on M 1 (III) oxidation state, each based on M 1 In this oxidation state, the metal ions can undergo redox reactions, such as through the TiO 2 Layer absorbs UV light and forms holes:
[0082] M 1 (III)+“+”→M 1 (IV)
[0083] In addition, most of the M1 2 O 3 The rare earth metal oxides are colorless or only slightly colored, while Ce 2 O 3 Has a strong golden hue. This allows the use of Ce 2 O 3 Compared with a large amount of M 1 2 O 3 (Here is the M used 1 2 O 3 The molar number of the base pearlescent pigment is less than 1%, and no strong color change occurs compared with the corresponding base pearlescent pigment.
[0084] Therefore, rare earth metal M 1 The content of the first metal oxide is in the range of 0.3-4.0 wt %, more preferably in the range of 0.5-3.0 wt %, most preferably in the range of 0.7-2.5 wt %, each based on the total amount of the pearlescent pigment.
[0085] This specific content depends largely on the fineness and thickness of the base pearlescent pigment, and finer and thinner base pearlescent pigments will have a higher specific surface area, which can be optimized by a person skilled in the art without unnecessary burden. Within these ranges, on the one hand, sufficient resistance to more stringent weathering test methods is achieved; on the other hand, the interference color change caused by the top coating is acceptable.
[0086] The amount of rare earth metal can be preferably detected by XRF (X-ray fluorescence analysis) and can be expressed as M 1 2 O 3 The weight % is based on the total amount of pearlescent pigments.
[0087] In some embodiments, the weatherable top coating also contains a very limited amount of cerium metal oxide. The amount of cerium oxide is preferably in the range of 0.0-30 wt %, more preferably in the range of 0.0-20 wt %, each as Ce 2 O 3 Calculated and calculated based on the total amount of rare earth metal oxides in the weather-resistant top coating and as M 1 2 O 3 The small amount may be acceptable in terms of color change compared to the base pearlescent pigment.
[0088] For silver-colored base pearlescent pigments, it is usually sufficient to use only a rare earth metal oxide coating as a single metal oxide coating in the top layer. Usually, such pigments have a rather low thickness of the high refractive index metal oxide of the base pearlescent pigment. For example, TiO based on a small transparent substrate 2 Coating, transparent silver pearlescent pigment with TiO 2 The thickness of the layer is about 40 nm. In this case, the photoactivity is not too high and a single rare earth coating is sufficient.
[0089] In the case of base pearlescent pigments with colored interference colors, the thickness and thus the content of high-refractive metal oxides, in particular Ti oxides, is relatively high, which generally leads to an increase in the optical activity. For these cases, it is recommended to use at least two metal oxide layers (variant b)). The first rare earth metal oxide layer is supplemented by a second metal oxide coating. The metal of this second metal oxide is metal M 2 , Metal M 2 Selected from Si, Al, Zn, Mg, Zr, Sn and mixtures thereof or combinations thereof.
[0090] A particularly preferred second metal oxide is SiO 2 、Al 2 O 3 、ZnO、MgO、ZrO 2 SnO 2 and mixtures or combinations thereof.
[0091] These materials are known in the art for use as weather-resistant top coating materials. They can be used as a mixture of two or more or as two or more separate layers. More preferred is SiO 2 、Al 2 O 3 、ZnO、ZrO 2 and mixtures thereof, most preferably SiO 2 , ZnO and mixtures thereof or combinations thereof. In particular, SiO 2 and ZnO, which are precipitated onto the pearlescent pigments as successive layers or mixed layers.
[0092] These metal oxides are all transparent in the visible light wavelength range, so their impact on the main color tone of the pearlescent pigment is very small.
[0093] Preferably, metal M 2 The amount of the second metal oxide is in the range of 1.0-5.0 wt %, more preferably in the range of 2.0-3.5 wt %, each based on the total amount of the pearlescent pigment.
[0094] As regards the sequence of the first metal oxide and the second metal oxide, in principle any sequence can be used.
[0095] In a first preferred embodiment, the first weather-resistant topcoat b) is structurally characterized in that the first coating layer on the base pearlescent pigment is a first rare earth metal oxide coating layer, followed by a second metal oxide coating layer.
[0096] Since these coatings have a thickness in the nanometer range, it may be difficult to analyze the specific sequence. Therefore, in a preferred embodiment, the weatherable top coating b) preferably has a structure obtained by first precipitating a precursor of a first rare earth metal oxide and then precipitating a precursor material of a second metal oxide.
[0097] In a further preferred embodiment, the weather-resistant top coating b) is structurally characterized in that the first rare earth metal oxide and the second metal oxide have been coprecipitated from precursors of the two metal oxides.
[0098] By employing such coprecipitation, the relative amounts of the various metal oxides in the topcoat layer can be varied slightly depending on the relative precipitation kinetics of the two precursor materials and the specific coating conditions. However, a mixed layer of the two metal oxides is necessarily included.
[0099] In a third embodiment, the structure of the weather-resistant top coating b) is characterized in that the first coating layer on the base pearlescent pigment is a coating layer of the second metal oxide, followed by a coating layer of the first rare earth metal oxide.
[0100] In either variant, the weatherable topcoat is modified by applying an organic modification. Such modifications are known in the art and are intended to make the surface of the pearlescent pigment compatible with the organic binder that is applied last when the pearlescent pigment is applied.
[0101] As such coupling agents, organofunctional silanes or water-based precondensed organofunctional silanes are used. These coupling agents have proven to be very effective and are well known in the art. These specific organofunctional silanes can be found in, for example, EP1682622 A1, EP 632109A1. For example, EP 0888410B1 and US2014 / 0018439 A1 describe precondensed organofunctional silanes in detail.
[0102] Method for preparing weather-resistant pearlescent pigment:
[0103] Another object of the present invention is to provide a method for preparing a weather-resistant pearlescent pigment, which comprises the following steps:
[0104] i) suspending the base pearlescent pigment in a solvent,
[0105] iia) coating the base pearlescent pigment in a solvent from step i) with a precursor of a rare earth metal oxide at a predetermined pH of 1 to obtain a rare earth metal oxide layer, or
[0106] iib) coating the base pearlescent pigment in solvent from step i) by one of the following methods:
[0107] iib1): using a precursor of a rare earth metal oxide at a predetermined pH 1 to obtain a rare earth metal oxide layer, and then coating the pearlescent pigment from this step with a precursor of a second metal oxide at a predetermined pH 2 to obtain a second metal oxide, or
[0108] iib2): using a precursor of a second metal oxide at a predetermined pH of 2 to form a second metal oxide, and then coating the pearlescent pigment with a precursor of a rare earth metal oxide at a predetermined pH of 1 to obtain a rare earth metal oxide layer, or
[0109] iib3): coating a precursor of a rare earth metal oxide together with a precursor of a second metal oxide at a predetermined pH 3, wherein the pH 3 is equal to or preferably between pH 1 and pH 2,
[0110] iii) coating the pearlescent pigment in solvent from step iia) or step iib) with an organofunctional silane or a water-based precondensed organofunctional silane, and
[0111] iv) isolating the coated pearlescent pigment, optionally washing with a solvent and drying at a temperature in the range of 80-160°C.
[0112] The base pearlescent pigment can be prepared according to known methods, and many base pearlescent pigments are commercially available.
[0113] The solvent can be water or an organic solvent. Preferred organic solvents are alcohols, such as methanol, ethanol, n-propanol, n-butanol, 2-methylpropanol, 2-methoxypropanol, butanediol, etc. Mixtures of any desired ratio of these alcohols can also be used. Preferred alcohol solvents are ethanol, isopropanol, or mixtures thereof.
[0114] Water is preferably used as solvent, and in this case, the precursor material for the rare earth metal oxide is preferably 1 Water-soluble salts of cations, usually chlorides, nitrates, sulfates, acetates, etc. The pH value can be stabilized by adding appropriate amounts of bases, such as NaOH or KOH, or acids, such as HCl or HNO 3 .
[0115] For the second metal oxide coating, preferably used is 2water glass, and chlorides or nitrates of Al, Zn, Zr, Mg or Sn.
[0116] M 1 The cation is preferably 50-100 mol% of M 1 (III) cations, more preferably 80-100 mol% of M 1 (III) cations, each based on M 1 The total amount of cations. They can be mixed with an appropriate amount of M 1 (IV) cation mixing. Generally, it is less preferred to use M 1 (IV) cations, since such cations generally have a distinct color.
[0117] When the solvent is an alcohol solvent, the precursor material for the rare earth metal oxide is also preferably 1 The corresponding salt of the cation which has sufficient solubility in the solvent (eg chloride, nitrate, acetate, octanoate, acetylacetonate). In this case, water is usually added to hydrolyze the metal cation.
[0118] As for the precursor of the second metal oxide, silane is generally used to form SiO 2 , such as tetramethoxysilane or tetraethoxysilane; for M 2 For other metals, salts such as chlorides, nitrates or acetonides are generally used.
[0119] The catalyst for the alcohol solvent is preferably a nitrogen-containing base. Examples thereof include ammonia, hydrazine, methylamine, ethylamine, triethanolamine, dimethylamine, diethylamine, methylethylamine, trimethylamine, triethylamine, ethylenediamine, trimethylenediamine, tetramethylenediamine, 1-propylamine, 2-propylamine, 1-butylamine, 2-butylamine, 1-propylmethylamine, 2-propylmethylamine, 1-butylmethylamine, 2-butylmethylamine, 1-propylethylamine, 2-propylethylamine, 1-butylethylamine, 2-butylethylamine, piperazine and pyridine.
[0120] The pH1 value for precipitating the rare earth metal oxide precursor is preferably in the range of 4.5-9.0, more preferably in the range of 5.0-8.5.
[0121] The pH 2 value for precipitating the second metal oxide precursor is preferably in the range of 5.0-9.0.
[0122] The temperature for the coating reaction is preferably in the range of 50°C to the boiling point of the solvent used, more preferably in the range of 55°C to 80°C.
[0123] As a drying step, step vi) can be carried out under ambient pressure or under vacuum.
[0124] Another object of the present invention is achieved by using weather-resistant pearlescent pigments in coatings, printing inks, plastics, powder coatings and in particular automotive primers.
[0125] A further embodiment of the present invention is a formulation, in particular an automotive basecoat formulation, comprising the weather-resistant pearlescent pigment.
[0126] A. Embodiment:
[0127] Embodiment 1:
[0128] 100 g of a commercially available silver pearlescent pigment based on synthetic mica with a fineness of 10-40 μm (Symic C604, Eckart GmbH) was suspended in 900 g of water. Subsequently, the dispersion was heated to 70° C. and 1.90 g of EuCl dissolved in 50 mL of water was added at pH 5.2. 3 *H 2 At the same time, the pH value was kept constant by adding a 10% KOH solution. Then, the pH value was raised to 7.5 with a 5 wt % KOH solution and stirred for 15 minutes.
[0129] Then, water glass solution (51.4 g water glass solution, 3.0 wt% SiO 2 (theoretical value represents the initial pearlescent pigment), mixed with 20.7 g of demineralized water), wherein the pH value was kept constant at pH 7.5.
[0130] After complete addition of the solution, the suspension was stirred for 1 hour and then a solution of 7.1 g of Hydrosil 2627 diluted with 24.3 g of demineralized water was added. After stirring for an additional 180 minutes, the suspension was filtered and the filter cake was washed with demineralized water and then dried at 95° C. and a vacuum of 100 mbar.
[0131] Embodiment 2:
[0132] 100 g of a commercially available silver pearlescent pigment based on synthetic mica with a fineness of 10-40 μm (Symic C604, Eckart GmbH) was suspended in 900 g of water. Subsequently, the dispersion was heated to 70° C. and 2.61 g of PrCl dissolved in 42 mL of water was added at pH 6.7. 3 *6H 2 At the same time, the pH value was kept constant by adding a 10% KOH solution. Then, the pH value was raised to 7.5 with a 5 wt % KOH solution and stirred for 15 minutes.
[0133] Then, water glass solution (51.4 g water glass solution, 3.0 wt% SiO 2(theoretical value represents the initial pearlescent pigment), mixed with 20.7 g of demineralized water), wherein the pH value was kept constant at pH 7.5.
[0134] After complete addition of the solution, the suspension was stirred for 1 hour and then a solution of 2.1 g of Dynasilan 1189 diluted with 14.7 g of isopropanol was added. After stirring for a further 180 minutes, the suspension was filtered and the filter cake was washed with demineralized water and then dried at 75° C. and a vacuum of 100 mbar.
[0135] Embodiment 3:
[0136] 100 g of a commercially available silver pearlescent pigment based on synthetic mica with a fineness of 10-40 μm (Symic C604, Eckart GmbH) was suspended in 900 g of water. Subsequently, the dispersion was heated to 70° C. and 3.06 g of Sm(NO) dissolved in 67 mL of water were added at pH 8.5. 3 ) 3 *6H 2 O. At the same time, the pH value was kept constant by adding 10% KOH solution. Then, water glass solution (51.4 g water glass solution, 3.0 wt% SiO 2 , mixed with 20.7 g of demineralized water), wherein the pH value was kept constant at pH 8.5.
[0137] After complete addition of the solution, the suspension was stirred for 1 hour and then a solution of 1.9 g Dynasilan 6490 diluted with 14.7 g isopropanol was added. After stirring for an additional 180 minutes, the suspension was filtered and the filter cake was washed with demineralized water and then dried at 75° C. and a vacuum of 100 mbar.
[0138] Embodiment 4:
[0139] 100 g of a commercially available silver pearlescent pigment based on synthetic mica with a fineness of 10-40 μm (Symic C604, Eckart GmbH) were suspended in 900 g of water. Subsequently, the dispersion was heated to 70° C. and 2.99 g of Gd(NO) dissolved in 65 mL of water were added at pH 5.5. 3 ) 3 *6H 2 At the same time, the pH value was kept constant by adding a 10% KOH solution. Then, the pH value was raised to 7.5 with a 5 wt % KOH solution and stirred for 15 minutes.
[0140] Then, water glass solution (51.4 g water glass solution, 3.0 wt% SiO 2, mixed with 20.7 g of demineralized water), wherein the pH value was kept constant at pH 7.5.
[0141] After complete addition of the solution, the suspension was stirred for 1 hour and then a solution of 5.7 g of Hydrosil 2776 diluted with 24.3 g of demineralized water was added. After stirring for an additional 180 minutes, the suspension was filtered and the filter cake was washed with demineralized water and then dried at 95° C. and a vacuum of 100 mbar.
[0142] Embodiment 5:
[0143] 100 g of a commercially available silver pearlescent pigment based on synthetic mica with a fineness of 10-40 μm (Symic C604, Eckart GmbH) was suspended in 900 g of water. Subsequently, the dispersion was heated to 70° C. and 2.37 g of YbCl dissolved in 65 mL of water was added at pH 6.7. 3 *6H 2 At the same time, the pH value was kept constant by adding a 10% KOH solution. Then, the pH value was raised to 7.5 with a 5 wt % KOH solution and stirred for 15 minutes.
[0144] Then, water glass solution (51.4 g water glass solution, 3.0 wt% SiO 2 , mixed with 20.7 g of demineralized water), wherein the pH value was kept constant at pH 7.5.
[0145] After complete addition of the solution, the suspension was stirred for 1 hour and then a solution of 7.1 g of Hydrosil 2627 diluted with 24.3 g of demineralized water was added. After stirring for an additional 180 minutes, the suspension was filtered and the filter cake was washed with demineralized water.
[0146] Embodiment 6:
[0147] 150 g of a commercially available silver pearlescent pigment based on synthetic mica with a fineness of 10-40 μm (Symic C604, Eckart GmbH) were suspended in 1200 g of water. Subsequently, the dispersion was heated to 70° C. and 2.87 g of NdCl dissolved in 60 mL of water were added at pH 6.5. 3 *H 2 At the same time, the pH value was kept constant by adding a 10% KOH solution. Then, the pH value was raised to 7.5 with a 5 wt % KOH solution and stirred for 15 minutes.
[0148] Then, water glass solution (77.1 g water glass solution, 3.0 wt% SiO 2, mixed with 31.0 g of demineralized water), wherein the pH value was kept constant at pH 7.5.
[0149] After complete addition of the solution, the suspension was stirred for 1 hour and then a solution of 9.65 g of Hydrosil 2627 diluted with 36.5 g of demineralized water was added. After stirring for an additional 180 minutes, the suspension was filtered and the filter cake was washed with demineralized water and then dried at 95° C. and a vacuum of 100 mbar.
[0150] Example 7 (alcohol type pathway):
[0151] 100 g of a commercially available silver pearlescent pigment based on synthetic mica (Symic C604, Eckart GmbH) with a fineness of 10-40 μm were suspended in 500 ml of isopropanol and brought to boiling point.
[0152] Under gentle stirring, 2.0 g H 2 O, then add 3.96g EuCl 3 *H 2 O in 20 g of isopropanol. Then, 0.45 g of ethylenediamine and 3.0 g of H 2 O. Then, 8.9 g of tetraethoxysilane and 21.0 g of isopropanol were added continuously over 2 hours using a metering pump. The suspension was then allowed to react for a further 6 hours. Subsequently, a solution of 2.1 g of Dynasilan 1189 in 12.9 g of isopropanol was added and heating was stopped. The resulting mixture was stirred overnight at room temperature, filtered and washed, and then dried at 95° C. and a vacuum of 100 mbar.
[0153] Embodiment 8:
[0154] 100 g of a commercially available silver pearlescent pigment based on synthetic mica with a fineness of 10-40 μm (Symic C604, Eckart GmbH) were suspended in 900 g of water. Subsequently, the dispersion was heated to 70° C. and 5.6 g of Gd(NO) dissolved in 75 mL of water were added at pH 5.5. 3 ) 3 *6H 2 At the same time, the pH value was kept constant by adding a 10% KOH solution. Then, the pH value was raised to 7.5 with a 5 wt % KOH solution and stirred for 15 minutes.
[0155] Then, water glass solution (42.8 g water glass solution, 2.5 wt% SiO 2 , mixed with 13.8 g of demineralized water), wherein the pH value was kept constant at pH 7.5.
[0156] After complete addition of the solution, the suspension was stirred for 1 hour and then a solution of 5.7 g of Hydrosil 2776 diluted with 24.3 g of demineralized water was added. After stirring for an additional 180 minutes, the suspension was filtered and the filter cake was washed with demineralized water and then dried at 95° C. and a vacuum of 100 mbar.
[0157] Embodiment 9:
[0158] 100 g of a commercially available silver pearlescent pigment based on synthetic mica with a fineness of 10-50 μm (Symic C604, Eckart GmbH) was suspended in 900 g of water. Subsequently, the dispersion was heated to 70° C. and 2.4 g of EuCl dissolved in 75 mL of water was added at pH 5.5. 3 *H 2 At the same time, the pH value was kept constant by adding a 10% KOH solution. Then, the pH value was raised to 7.5 with a 5 wt % KOH solution and stirred for 15 minutes.
[0159] Then, water glass solution (42.8 g water glass solution, 6.0 wt% SiO 2 , mixed with 13.8 g of demineralized water), wherein the pH value was kept constant at pH 7.5.
[0160] After complete addition of the solution, the suspension was stirred for 1 hour and then a solution of 2.0 g of Dynasilan 4148 diluted with 24.3 g of demineralized water was added. After stirring for an additional 180 minutes, the suspension was filtered and the filter cake was washed with demineralized water and then dried at 95° C. and a vacuum of 100 mbar.
[0161] Embodiment 10:
[0162] 100 g of a commercially available silver pearlescent pigment based on synthetic mica with a fineness of 10-50 μm (Symic C604, Eckart GmbH) was suspended in 900 g of water. Subsequently, the dispersion was heated to 70° C. and 4.0 g of EuCl dissolved in 75 mL of water was added at pH 5.5. 3 *H 2 At the same time, the pH value was kept constant by adding a 10% KOH solution. Then, the pH value was raised to 7.5 with a 5 wt % KOH solution and stirred for 15 minutes.
[0163] Then, water glass solution (42.8 g water glass solution, 6.0 wt% SiO 2 , mixed with 13.8 g of demineralized water), wherein the pH value was kept constant at pH 7.5.
[0164] After complete addition of the solution, the suspension was stirred for 1 hour and then a solution of 5.7 g of Hydrosil 2776 diluted with 24.3 g of demineralized water was added. After stirring for an additional 180 minutes, the suspension was filtered and the filter cake was washed with demineralized water and then dried at 95° C. and a vacuum of 100 mbar.
[0165] Embodiment 11:
[0166] 100 g of a commercially available red pearlescent pigment based on titanium dioxide-coated glass flakes with a fineness of 10-60 μm (Luxan C241, Eckart GmbH) were suspended in 800 g of water. Subsequently, the dispersion was heated to 70° C. and 3.06 g of Sm(NO) dissolved in 67 mL of water were added at pH 8.5. 3 ) 3 *6H 2 O. At the same time, the pH value was kept constant by adding 10% KOH solution. Then, water glass solution (51.4 g water glass solution, 6.0 wt% SiO 2 , mixed with 20.7 g of demineralized water), wherein the pH value was kept constant at pH 8.5.
[0167] After complete addition of the solution, the suspension was stirred for 1 hour and then a solution of 1.7 g Dynasilan 6490 diluted with 14.7 g isopropanol was added. After stirring for an additional 180 minutes, the suspension was filtered and the filter cake was washed with demineralized water and then dried at 75° C. and a vacuum of 100 mbar.
[0168] Embodiment 12:
[0169] 100 g of a commercially available silver pearlescent pigment based on synthetic mica with a fineness of 10-50 μm (Symic C604, Eckart GmbH) was suspended in 900 g of water. Subsequently, the dispersion was heated to 70° C. and 2.4 g of EuCl dissolved in 75 mL of water was added at pH 5.5. 3 *H 2 At the same time, the pH value was kept constant by adding a 10% KOH solution. Then, the pH value was raised to 7.5 with a 5 wt % KOH solution and stirred for 15 minutes.
[0170] Then, water glass solution (51.4 g water glass solution, 6.0 wt% SiO 2 , mixed with 13.8 g of demineralized water), wherein the pH value was kept constant at pH 7.5.
[0171] After complete addition of the solution, the suspension was stirred for 1 hour and then a solution of 2.0 g of Dynasilan 1189 diluted with 24.3 g of isopropanol was added. After stirring for an additional 180 minutes, the suspension was filtered and the filter cake was washed with demineralized water and then dried at 95° C. and a vacuum of 100 mbar.
[0172] Embodiment 13:
[0173] 100 g of a commercially available silver pearlescent pigment based on titanium dioxide-coated synthetic mica with a fineness of 10-50 μm (Symic C001, Eckart GmbH) was suspended in 900 g of water. Subsequently, the dispersion was heated to 70° C. and 2.2 g of Gd(NO) dissolved in 75 mL of water was added at pH 5.5. 3 ) 3 *6H 2 At the same time, the pH value was kept constant by adding a 10% KOH solution. Then, the pH value was raised to 7.5 with a 5 wt % KOH solution and stirred for 15 minutes.
[0174] Then, water glass solution (11.4 g water glass solution, 6.0 wt% SiO 2 , mixed with 13.8 g of demineralized water), wherein the pH value was kept constant at pH 7.5.
[0175] After complete addition of the solution, the suspension was stirred for 1 hour and then a solution of 2.0 g of Dynasilan 1189 diluted with 24.3 g of isopropanol was added. After stirring for an additional 180 minutes, the suspension was filtered and the filter cake was washed with demineralized water and then dried at 95° C. and a vacuum of 100 mbar.
[0176] Embodiment 14:
[0177] 150 g of a commercially available silver pearlescent pigment based on synthetic mica with a fineness of 10-40 μm (Symic C604, Eckart GmbH) was suspended in 1200 g of water. Subsequently, the dispersion was heated to 70° C. and 1.27 g of ZnCl dissolved in 60 mL of water was added at pH 6.5. 2 At the same time, by adding water glass solution (28.2g water glass solution, 6.0wt% SiO 2 , mixed with 31.0 g of demineralized water) to keep the pH value constant.
[0178] Subsequently, 3.47 g of Sm(NO) dissolved in 67 mL of water was added. 3 ) 3 *6H 2At the same time, the pH value was kept constant by adding 10% KOH solution.
[0179] After complete addition of the solution, the suspension was stirred for 1 hour and then a solution of 9.65 g of Hydrosil 2627 diluted with 36.5 g of demineralized water was added. After stirring for an additional 180 minutes, the suspension was filtered and the filter cake was washed with demineralized water and then dried at 95° C. and a vacuum of 100 mbar.
[0180] Embodiment 15:
[0181] 100 g of a commercially available silver pearlescent pigment based on titanium dioxide and iron oxide coated synthetic mica with a fineness of 10-50 μm (Symic C604, Eckart GmbH) was suspended in 900 g of water. Subsequently, the dispersion was heated to 70° C. and 2.4 g of EuCl dissolved in 75 mL of VE water was added at pH 5.5. 3 *H 2 O. At the same time, the pH value was kept constant by adding 10% KOH solution. Then, the pH value was raised to 7.5 with 5 wt% KOH solution and stirred for 15 minutes. Then, 12.0 g of zinc chloride solution was added, wherein w(ZnCl 2 )=7.0%,and 8.5 wt% SiO 2 of water glass solution to maintain the pH at 7.5.
[0182] After complete addition of the solution, the suspension was stirred for 90 minutes and then a solution of 6.43 g of Hydrosil 2627 diluted with 30 g of demineralized water was slowly added. The suspension was stirred for a further 17 hours at 70° C. and subsequently filtered, and the filter cake was washed with demineralized water and then dried at 95° C. and a vacuum of 100 mbar.
[0183] Embodiment 16:
[0184] 100 g of a commercially available silver pearlescent pigment based on titanium dioxide and iron oxide coated synthetic mica (Symic C604, Eckart GmbH) with a fineness of 10-50 μm was suspended in 900 g of water. Subsequently, the dispersion was heated to 70° C. and 12.0 g of a zinc chloride solution was added, wherein w(ZnCl 2 )=7.0%. By continuously adding 8.5 wt% SiO 2 of water glass solution and adjust the pH to 7.0.
[0185] After complete addition of the solution, the suspension was stirred for 1 hour and then the pH was adjusted to 8.5. Subsequently, 3.06 g of Sm(NO) dissolved in 67 mL of VE water was added.3 ) 3 *6H 2 At the same time, the pH value was kept constant by adding 10% KOH solution. After complete addition of the solution, the suspension was stirred for 1 hour and then a solution of 1.9 g Dynasilan 6490 diluted with 10 g isopropanol was added. After additional stirring for 180 minutes, the suspension was filtered and the filter cake was washed with demineralized water and then dried at 95° C. and a vacuum of 100 mbar.
[0186] Embodiment 17:
[0187] 100 g of a commercial pearlescent pigment based on titanium dioxide-coated synthetic mica with a fineness of 10-50 μm and red interference (Symic C241, Eckart GmbH) was suspended in 900 g of water. Subsequently, the dispersion was heated to 70° C. and the pH value was adjusted to 7.5, and then 1.28 g of Sm(NO) dissolved in 28 mL of demineralized water was added. 3 ) 3 *6H 2 O. At the same time, the pH value was kept constant by adding 10% KOH solution. After stirring for 15 minutes, 12.0 g of zinc chloride solution was added, wherein w(ZnCl 2 )=7.0%,and 8.5 wt% SiO 2 A water glass solution of 100 g was added to keep the pH at 7.5. After complete addition of the solution, the suspension was stirred for a further 90 minutes and then a solution of 6.43 g of Hydrosil 2627 diluted with 30 g of demineralized water was slowly added. The suspension was stirred for a further 17 hours at 70° C., then filtered, and the filter cake was washed with demineralized water and then dried at 95° C. and a vacuum of 100 mbar.
[0188] Comparative Example 1: (according to EP 1682622 A1)
[0189] 150 g of a commercially available silver pearlescent pigment based on synthetic mica with a fineness of 10-50 μm (Symic C604, Eckart GmbH) was suspended in 1200 g of water. Subsequently, the dispersion was heated to 70° C. and 4.76 g of CeNO dissolved in 60 mL of water was added at pH 6.5. 3 *6H 2 At the same time, the pH value was kept constant by adding a 10% KOH solution. Then, the pH value was raised to 7.5 with a 5 wt % KOH solution and stirred for 15 minutes.
[0190] Subsequently, water glass solution (77.1 g of water glass solution, containing 6.0 wt % SiO2 , mixed with 31.0 g of demineralized water), wherein the pH value was kept constant at 7.5.
[0191] After complete addition of the solution, the suspension was stirred for 1 hour and then a solution of 9.65 g of Hydrosil 2627 diluted with 36.5 g of demineralized water was added. After stirring for an additional 180 minutes, the suspension was filtered and the filter cake was washed with demineralized water and then dried at 95° C. and a vacuum of 100 mbar.
[0192] Comparative Example 2: (according to US2014 / 018439 A1)
[0193] 150 g of a commercially available silver pearlescent pigment based on titanium dioxide-coated synthetic mica with a fineness of 10-50 μm (Symic C604, Eckart GmbH) was suspended in 1200 g of water. Subsequently, the dispersion was heated to 70° C. and 3.60 g of CeNO dissolved in 60 mL of water was added at pH 6.5. 3 *6H 2 At the same time, the pH value was kept constant by adding 10% KOH solution. The dispersion was stirred for a further hour and then the pH value was raised to 7.5 by adding 10% KOH solution. A solution of 5.7 g of Hydrosil 2776 diluted with 24.3 g of demineralized water was added. After an additional 180 minutes of stirring, the suspension was filtered and the filter cake was washed with demineralized water and then dried at 95° C. and a vacuum of 100 mbar.
[0194] Comparative Example 3:
[0195] A commercially available silver pearlescent pigment based on titanium dioxide-coated synthetic mica with a particle size of 10-50 μm was used, which was Symic C001 (D 50 22 μm), but without a weather-resistant top coating.
[0196] Comparative Example 4:
[0197] A commercially available silver opaque pearlescent pigment with a fineness of 10-50 μm using synthetic mica as a substrate was used, which was Symic C604 (D 50 22 μm), but without a weather-resistant top coating.
[0198] Comparative Example 5: (according to EP 1682622 A1)
[0199] 150 g of commercially available silver pearlescent pigment (Symic C604, Eckart GmbH) was suspended in 1200 g of water. Subsequently, the dispersion was heated to 70° C. and 1.19 g of CeNO dissolved in 50 mL of VE water was added at pH 6.5. 3 *6H 2 At the same time, the pH value was kept constant by adding 10% KOH solution. Then, the pH value was raised to 7.5 with 5 wt % KOH solution and stirred for 15 minutes.
[0200] Subsequently, water glass solution (25.7 g water glass solution, 6.0 wt% SiO 2 , mixed with 31.0 g of demineralized water), wherein the pH value was kept constant at pH 7.5.
[0201] After complete addition of the solution, the suspension was stirred for 1 hour and then a solution of 2.25 g of Dynasilan 6490 diluted with 36.5 g of demineralized water was added. After stirring for an additional 180 minutes, the suspension was filtered and the filter cake was washed with demineralized water and then dried at 95° C. and a vacuum of 100 mbar.
[0202] Comparative Example 6:
[0203] A commercially available red pearlescent pigment based on titanium dioxide-coated glass flakes with a particle size of 10-60 μm was used, which was Luxan C241 (D 50 29 μm), but without a weather-resistant top coating.
[0204] All test results are summarized in Table 1 regarding the composition of the top coating.
[0205] Table 1: Test parameters and composition of top coatings of samples
[0206]
[0207]
[0208] * XRF testing; if not otherwise specified, as M 2 O 3 Calculation, unit is weight %;
[0209] **Theoretical amount, in weight %, relative to the amount of the base pearlescent pigment;
[0210] *** Measured by XRF and calculated as ZnO in weight %.
[0211] B. Detection method:
[0212] B1. Photocatalytic activity:
[0213] To determine the photocatalytic activity of the pigment powders, a specific gas phase photoreactor was used, e.g. Figure 1 As shown in the schematic diagram.
[0214] 150 mg of the pigment powder was weighed and placed in the center of a petri dish, and then the petri dish was placed at the bottom of the photoreactor. The temperature of the photoreactor was adjusted and kept constant at 50°C.
[0215] The photoactivity of these samples was measured in ambient air, where an air pump was used to circulate ambient air through the FTIR detection system and back to the photoreactor. The initial water content and CO 2 The contents are approximately 0.2% and 400 ppm respectively.
[0216] As a model contaminant, 1 μL of acetone was injected onto the septum inside the system. After the contaminant was evenly distributed, the UV lamp (90 mW / cm at 405 nm) was turned on. 2 ), acetone begins to decompose and quantitatively forms CO 2 .
[0217] Monitoring the decomposition of acetone and CO over time using FTIR spectroscopy 2 The formation of acetone and carbon dioxide was linearly approximated to obtain the formation rate in ppm / h.
[0218] CO 2 The higher the formation rate (in ppm / h), the higher the photocatalytic activity of the pigment powder. 2 The test is passed if the formation rate is less than 3 ppm / h.
[0219] For each test series, a zero spectra was previously performed, in which the same procedure was followed, but no pigment was used and no acetone was injected. The blank values were subtracted from the values of the pigmented samples.
[0220] B2: Color shade durability and optical properties of samples compared to initial material without top coating:
[0221] The samples were coated by a knife-down method onto a black-white opacity chart (Byko-Chart 2853, Bykgardner), using a 40 μm spiral rod for the synthetic mica-based samples and a 50 μm spiral rod for the glass flake-based samples. The effect pigments were dispersed in a conventional nitrocellulose coating (Dr. Renger Erco bronze hybrid varnish 2615e; from Morton, 6.0 wt. % pigment based on the total weight of the wet varnish). The color change in diffuse reflection was measured using a MINOLTA CM-700d compared to the respective samples without a weather-resistant topcoat. The color values on the white part of the above opacity chart were measured and the differences were expressed using the known Hunter formula:
[0222] △E*=(△L* 2 +△a* 2 +△b* 2 ) 1 / 2
[0223] These differences are indicative of the change in the primary color tone of the pearlescent pigment. An overall color change value of ΔE*≤2.25 is acceptable.
[0224] B3. Double coating air gun coating:
[0225] Aluminum test panels with white bases were coated with a 1K water-based test basecoat varnish containing an acrylate-polyurethane binder and 1.5% by weight of the pearlescent pigments of the above examples and comparative examples using an Oerter APL1.2 air gun. The wet thickness of the coating was 13-17 μm and the coated panels were dried at 80° C. for 12 minutes.
[0226] A 1K conventional acrylate type clearcoat was used as a clearcoat with a thickness of 37-43 μm and dried for 30 minutes at a temperature of 140° C. Using a 1K clearcoat instead of a conventional 2K clearcoat enabled the test conditions to be improved.
[0227] B4. Weathering resistance test (combined xenon and condensation water test):
[0228] The panels were subjected to a xenon-accelerated weathering test for 1000 hours in accordance with SAE J 2527. The panels were then directly subjected to a condensation water test in accordance with DIN EN ISO 6270-2 at 40° C. for 72 hours.
[0229] Before and after the test, the gloss was measured using a 20° gloss meter (Micro-TRI-Gloss from BYKgardenergmbH) according to DIN EN ISO 2813 and expressed as % difference compared to the gloss before the test. A reduction in relative gloss of less than -40% is acceptable.
[0230] Sometimes, this test is only performed after the photocatalytic activity test and the color change test have been passed.
[0231] B5. Detection of carbon content:
[0232] The carbon content of all samples was determined by burning the samples in an oxygen stream and detecting the released CO by IR spectroscopy using an analyzer from LECOInstrument GmbH, Germany. 2 And measured.
[0233] B6.XRF analysis:
[0234] The samples of Example 14 and some pigments from the comparative examples were tested for their metal oxides and Zn content of rare earth metals using x-ray fluorescence analysis (XRF). For this purpose, the corresponding pigments were added to lithium tetraborate glass sheets, fixed in solid sample test cups, and analyzed. The test instrument used was an AdvantixARL system from Thermo Scientific. The test results were first calibrated using appropriate standard methods. The results are listed in Table 1.
[0235] The Si content of the top coating of these samples could not be determined by this method, since the transparent synthetic mica or glass substrate already has a high content of silica. Instead, theoretical values are shown in Table 1 when a reaction rate of 100% is assumed.
[0236] C. Results:
[0237] The test results are shown in Table 2.
[0238] Table 2: Test results of samples
[0239]
[0240] D. Discussion:
[0241] All of the inventive examples passed the photoactivity test very well, with low delta E* changes, and passed the combined xenon and condensed water tests. Comparative Example 7, which had no weatherable topcoat at all and was a green pearlescent pigment, failed the photoactivity test. Likewise, Comparative Examples 3 and 4, which used silver pearlescent pigments, also failed the test.
[0242] Comparative Examples 1 and 5 were prepared according to EP 1682622 A1 and both passed the photoactivity test. Comparative Example 1 also passed the combined xenon and condensed water test, while Comparative Example 5 did not pass this test. However, Comparative Example 1 had a neutral anthracite color hue and did not pass the color change ΔE* test, especially when compared to Examples 1-8 and Example 10. This can be attributed to the use of a larger amount of Ce 2 O 3 And this cerium oxide has a light yellow color. Comparative Example 5 can pass the color change test (ΔE* is comparable to Example 12 using the same base pearlescent pigment), which is obviously due to the Ce 2 O 3 However, it seems that Ce 2 O 3 Too low a dosage results in failure of the combined xenon and condensed water test.
[0243] Example 13 represents a silver pearlescent pigment with only a single metal oxide layer (Gd 2 O 3 ) coating. This sample also passed all the tests, although the photoactivity was slightly higher than most of the other examples. In contrast, Comparative Example 2 has a single Ce 2 O 3 top coating and did not pass the photoactivity test.
[0244] Examples 15 and 17 performed particularly well in the combined xenon and condensed water test.
[0245] The carbon content of all examples is very low, indicating that only a portion of the silane used for surface modification has been bound to the surface of the pigment. Without being bound by any theory, the inventors believe that the effect of this low carbon content in the non-hydrophobic surface contributes to passing the combined xenon and condensed water test.
Claims
1. A weather-resistant pearlescent pigment having a base pearlescent and an interference color, the pigment comprising a transparent platelet-shaped substrate and at least one metal oxide layer having a refractive index > 1.8, and having a weather-resistant top coating on top of the base pearlescent pigment, the weather-resistant top coating comprising at least one metal oxide and an organic functional surface modification, wherein a) For a base pearlescent pigment having a silver interference color, the weather-resistant top coating is composed of a rare earth metal M selected from Y, La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu and mixtures thereof 1 A first metal oxide composition, or b) For base pearlescent pigments with colored interference colors or silver interference colors, the weather-resistant top coating comprises a rare earth metal M selected from Y, La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu and mixtures thereof. 1 A first metal oxide, and a second metal M selected from Si, Al, Zn, Mg, Zr, Sn and a mixture or a combination thereof 2 A second metal oxide, And in each case of a) or b), the organofunctional surface modification comprises an organofunctional silane or a water-based precondensed organofunctional silane.
2. The weather-resistant pearlescent pigment according to claim 1, wherein the weather-resistant top coating layer comprises a metal oxide of a rare earth metal selected from La, Pr, Nd, Sm, Eu, Gd, Ho, Yb and mixtures thereof.
3. The weather-resistant pearlescent pigment according to claim 1 or 2, wherein the weather-resistant top coating layer comprises a metal oxide of a rare earth metal selected from the group consisting of Nd, Sm, Yb, Eu, Ga and mixtures thereof.
4. The weather-resistant pearlescent pigment according to any one of the preceding claims, wherein the metal M 2 The second metal oxide is selected from SiO2, Al2O3, ZnO, MgO, ZrO2, SnO2, and mixtures thereof or combinations thereof.
5. The weather-resistant pearlescent pigment according to any one of the preceding claims, wherein the 1 ions, 50-100 atomic % of rare earth metal M 1 Metal oxides are based on M 1 (III) Oxidation state.
6. The weather-resistant pearlescent pigment according to any one of the preceding claims, wherein the rare earth metal M 1 The content of the first metal oxide is in the range of 0.3-3.0 wt%.
7. The weather-resistant pearlescent pigment according to any one of the preceding claims, wherein the weather-resistant top coating further comprises 0.0-30 wt. % of cerium metal oxide, calculated as Ce2O3 and based on the total amount of the rare earth weather-resistant top coating and as M 1 2O3 calculation.
8. The weather-resistant pearlescent pigment according to any one of the preceding claims, wherein the metal M 2 The content of the second metal oxide is in the range of 1.0-4.0 wt%.
9. The weather-resistant pearlescent pigment according to any one of the preceding claims, wherein the weather-resistant top coating b) is characterized in that the first coating layer on the high refractive index metal oxide coating layer is a first rare earth metal oxide coating layer, followed by a second metal oxide coating layer.
10. The weather-resistant pearlescent pigment according to any one of claims 1 to 9, wherein the structural feature of the weather-resistant top coating b) is that the first rare earth metal oxide and the second metal oxide have been prepared by coprecipitation from precursors of the two metal oxides.
11. The weather-resistant pearlescent pigment according to any one of the preceding claims, wherein the transparent platelet-shaped substrate from the base pearlescent pigment is selected from natural mica, synthetic mica platelets, glass platelets, SiO2 platelets, Al2O3 platelets, synthetic boehmite platelets, BiOCl platelets and mixtures thereof.
12. A method for preparing the weather-resistant pearlescent pigment according to claims 1-11, comprising the following steps: i) suspending the base pearlescent pigment in a solvent, iia) coating the base pearlescent pigment in a solvent from step i) with a precursor of a rare earth metal oxide at a predetermined pH of 1 to obtain a rare earth metal oxide layer, or iib) coating the base pearlescent pigment in solvent from step i) by one of the following methods: iib1): using a precursor of a rare earth metal oxide at a predetermined pH 1 to obtain a rare earth metal oxide layer, and then coating the pearlescent pigment from this step with a precursor of a second metal oxide at a predetermined pH 2 to obtain a second metal oxide, or iib2): using a precursor of a second metal oxide at a predetermined pH of 2 to obtain a second metal oxide, and then coating the pearlescent pigment with a precursor of a rare earth metal oxide at a predetermined pH of 1 to obtain a rare earth metal oxide layer, or iib3): coating is performed using a precursor of a rare earth metal oxide together with a precursor of a second metal oxide at a predetermined pH 3, wherein the pH 3 is equal to or preferably between pH 1 and pH 2, iii) coating the pearlescent pigment in solvent from step iia) or step iib) with an organofunctional silane or a water-based precondensed organofunctional silane, and iv) isolating the coated pearlescent pigment, optionally washing with a solvent and drying at a temperature in the range of 80-160°C.
13. The method according to claim 12, wherein the solvent can be water or an organic solvent, preferably an alcohol solvent; wherein for aqueous solvents, the rare earth metal M 1 The amount of the salt of the cation (III) is based on M 1 50-100 mol % of the total amount of cations; and wherein for the organic solvent, the rare earth metal M 1 (III) a salt of a cation or a rare earth metal M 1 (III) Cationic metal organic compounds are used as precursor materials.
14. Use of the weather-resistant pearlescent pigments according to claims 1 to 11 in coatings, printing inks, plastics, powder coatings and especially automotive primers.
15. A formulation comprising the weather-resistant pearlescent pigment according to claims 1 to 11, in particular a primer formulation.
Citation Information
Patent Citations
Weather-resistant nacreous pigments
EP0141174A1
Method and apparatus for glass flakes
EP0289240A1
Method and apparatus for glass flakes
EP0289240B1
Nacreous pigment for aqueous lacquering system
EP0632109A1
Improved weather resistant pearlescent pigments
EP0649886A2